2021
DOI: 10.14309/ajg.0000000000001185
|View full text |Cite
|
Sign up to set email alerts
|

The Time Is Now to Understand and Address Sex-Related Disparities in Gastroenterology and Hepatology

Abstract: Many gastrointestinal disorders, autoimmune diseases, and pregnancy-related conditions preferentially impact women. This issue of The American Journal of Gastroenterology focuses on women's health in the context of gastrointestinal and liver disease. This editorial highlights the current issue's contents and seeks to spark the conversations to bring awareness to the many issues faced by women as both patients and practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To help address this shortcoming, we dedicated the March 2021 issue to women's health and published a collection of high-impact essays and original investigations exploring the differential impact of digestive diseases on women. In their accompanying editorial to the special issue, Associate Editors Aasma Shaukat and Amy Oxentenko concluded that "what we hope to see in our lifetime is the recognition, attention, transparency, inclusivity, and solutions to address many issues faced by women who are our patients in gastroenterology, but as importantly, for women who will serve and lead in the profession of gastroenterology" (44).…”
mentioning
confidence: 99%
“…To help address this shortcoming, we dedicated the March 2021 issue to women's health and published a collection of high-impact essays and original investigations exploring the differential impact of digestive diseases on women. In their accompanying editorial to the special issue, Associate Editors Aasma Shaukat and Amy Oxentenko concluded that "what we hope to see in our lifetime is the recognition, attention, transparency, inclusivity, and solutions to address many issues faced by women who are our patients in gastroenterology, but as importantly, for women who will serve and lead in the profession of gastroenterology" (44).…”
mentioning
confidence: 99%